IRF5 is a specific marker of inflammatory macrophages in vivo. - Weiss, M; Blazek, K; Byrne, A; Byrne, A; Perocheau, D; Udalova, I (Hindawi Publishing Corporation, 2013)
Macrophages are an integral part of the innate immune system and key players in pathogen clearance and tissue remodelling. Both functions are accomplished by a pivotal network of different macrophage subtypes, including proinflammatory M1 and anti-inflammatory M2 macrophages. Previously, our laboratory identified the transcription factor interferon regulatory factor 5 (IRF5) as the master regulator of the M1 macrophage polarisation. IRF5 was found to be highly expressed in human M1 compared to M2 macrophages. Furthermore, IRF5 dictates the expression of proinflammatory genes such as IL12b and IL23a whilst repressing anti-inflammatory genes like IL10. Here we show that murine bone marrow derived macrophages differentiated in vitro with GM-CSF are also characterised by high levels of IRF5 mRNA and protein and express proinflammatory cytokines upon LPS stimulation. These macrophages display characteristic expression of M1-marker MHC II but lack the M2-marker CD206. Significantly, we develop intracellular staining of IRF5- expressing macrophages and utilise it to recapitulate the in vitro results in an in vivo model of antigen-induced arthritis, emphasising their physiological relevance. Thus, we establish the species-invariant role of IRF5 in controlling the inflammatory macrophage phenotype both in vitro and in in vivo.